2016
DOI: 10.12973/eurasia.2016.1241a
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Frogs among High School Students: Influences of Disgust and Culture

Abstract: Amphibians play an important role in the functioning of ecosystems and some of them inhabit human gardens where they can successfully reproduce. The decline of amphibian diversity worldwide suggests that people may play a crucial role in their survival. We conducted a cross-cultural study on high school students' tolerance of frogs in Chile, Slovakia, South Africa and Turkey (n = 655 high school students). We found that about 6 % of students reported active killing of frogs and 30 % reported moving frogs away … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 35 publications
1
20
0
7
Order By: Relevance
“…On the other hand, famers with a domination wildlife value orientation were not likely to kill wildlife, in response to crop damage. The low predictive power of domination can underlie the existence of other important drivers of wildlife killing by farmers, e.g., emotions towards wildlife (Manfredo 2008;Jacobs 2012;Jacobs et al 2012Jacobs et al , 2014aFrank et al 2016;Prokop et al 2016). In our study, the majority of respondents (c. 62%) had suffered crop damaging prior to the questionnaire and we believe that the existence, the extent, and the frequency of previous crop damaging can be other important factors guiding decision-making.…”
Section: Discussionmentioning
confidence: 70%
“…On the other hand, famers with a domination wildlife value orientation were not likely to kill wildlife, in response to crop damage. The low predictive power of domination can underlie the existence of other important drivers of wildlife killing by farmers, e.g., emotions towards wildlife (Manfredo 2008;Jacobs 2012;Jacobs et al 2012Jacobs et al , 2014aFrank et al 2016;Prokop et al 2016). In our study, the majority of respondents (c. 62%) had suffered crop damaging prior to the questionnaire and we believe that the existence, the extent, and the frequency of previous crop damaging can be other important factors guiding decision-making.…”
Section: Discussionmentioning
confidence: 70%
“…In relation to gender, the studies are not conclusive, because many results showed no differences between men and women (Ohemeng et al, 2017; Shafie et al, 2017; De Prada and Barragán Tabares 2018; Musila et al, 2018. However, considering that that frogs are unpopular like bats, it was found that women show greater tolerance to frogs than men (Prokop et al, 2016). While some studies suggest that the occupation or work task does not significantly affect the perceptions and attitudes towards the species (Shafie et al, 2017), other authors argue that people can evaluate and value wildlife according to their daily routine and where they live and work (Miller and Hobbs, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear if lack of accurate knowledge was driven by disliking frogs or if disliking frogs meant that individuals were disinterested in accurate knowledge. Many previous studies have determined that direct experiences of animals, pets, and nature increases the retention of knowledge about these creatures and improves attitudes [37]. Those who reported direct positive experiences with frogs in their childhood also scored higher on knowledge and beliefs and this may be a precursor to retaining accurate knowledge.…”
Section: Knowledgementioning
confidence: 89%
“…and it was most likely to be classified as "gross". The dislike of the rain frog is likely triggered by a strong disgust reflex which has been demonstrated as the primary driver for frog dislike amongst Slovakian respondents [37,45]. Those that liked the rain frog, tended to laugh at it and see it as 'funny' or 'grumpy', personifying its ugliness into something relatable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation